Efeitos do bisfenol A nas glândulas salivares de camundongos e em linhagem de células tumorais humanas. - Gabriela Kelly da Silva (2023)
Bisphenol A (BPA) is an endocrine-disrupting chemical with potential role in endocrine cancers. However, BPA effects on the salivary glands have been barely explored. We investigated the impact of in vivo sub-chronic exposure to BPA and its in vitro effects on salivary gland mucoepidermoid carcinoma cell lines. Male and female mice were exposed to BPA (30,000 μg/kg/day). We analyzed sublingual and submandibular salivary glands from sham C56BL6 mice and that female ones underwent ovariectomy. Concentration of BPA in salivary glands was evaluated by gas chromatography coupled to ion trap mass spectrometry. Expression of ERα and ERβ receptors was assessed in mouse salivary gland samples and cell lines UM-HMC-1 and UM-HMC-3A by qRT-PCR, mARN. In vitro, cell viability p63 and Ki-67 immunostaining and expression of target proteins related to survival/proliferation pathways were evaluated. BPA impaired the architectural of the submandibular and sublingual glands, particularly in female mice, and increased the expression of estrogen receptors. This was accompanied by a significant accumulation of BPA in these tissues. Conversely, the reduction of estrogen levels by the ovariectomy model slightly impacted BPA-induced morphological changes. In vitro, BPA did not affect the proliferation of neoplastic cells, but increased the expression of p63 and estrogen receptors. ERK1/2 phosphorylation was increased while AKT and NF-κB phosphorylation was reduced. Data highlight a harmful effect of BPA on salivary gland tissues and tumorigenic cells. Estrogen-dependent may orchestrate the BPA-accumulation mechanism, along with pro-survival signaling pathway and increased p63 expression.